Determinasi Makroekonomi terhadap IPM Indonesia: Analisis ARDL dan Relevansi Maqashid al-Shariah dalam Kebijakan Fiskal (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2026)
This study aims to analyze the influence of macroeconomic indicators on the Human Development Index (HDI) in Indonesia from an Islamic economic perspective. This research employs a quantitative approach using the Autoregressive Distributed Lag (ARDL) model with time series data from 1991 to 2022. The variables examined include inflation, economic growth (GDP), government expenditure, and unemployment rate. The results show that all variables simultaneously affect HDI. Partially, economic growth has a positive and significant effect on HDI in both the short and long term. Inflation has a positive and significant effect in the short term, while government expenditure does not have a significant effect on HDI. Meanwhile, the unemployment rate has a negative and significant effect in the long term. These findings highlight the importance of maintaining sustainable economic growth, managing unemployment effectively, and optimizing government expenditure policies in line with maqashid al-shariah principles to enhance the quality of human development in Indonesia.